Pure Electric Vehicle using Hybrid Energy Storage System - Singh, Ojaswa pratap; Yadav, Rakesh Kumar (International Journal of Membrane Science and Technology, 2023)
The improvement of energy storage capability of pure electric vehicles (PEVs) is a crucial factor in promoting sustainable transportation. Hybrid Energy Storage Systems (HESS) have emerged as a promising solution to address the energy storage limitations of PEVs. HESS combines two or more energy storage devices with complementary characteristics to optimize the power and energy density of the system. The use of HESS in PEVs allows for efficient energy management, reducing the overall weight, cost, and volume of the system while improving its performance. Additionally, HESS can be integrated with advanced energy management systems to further optimize the energy consumption of the vehicle. This paper reviews the use of HESS in PEVs and its potential to improve the energy storage capability of these vehicles. It discusses the advantages of using HESS, such as reducing the battery size and improving the energy efficiency and driving range of the vehicle. The paper also presents several studies that demonstrate the effectiveness of using HESS in PEVs, especially when combined with energy-saving strategies. The results of these studies show that HESS has the potential to significantly improve the performance of PEVs, which can help to accelerate the adoption of EVs and promote sustainable transportation.